Application of Organic Architecture in School of Nature Design - S O Hamsan; E Poedjioetami; F H Hendra (Institut Teknologi Sepuluh Nopember, 2018)
The development of education in the room is the main factor for students to feel the boredom of learning in the room. Indoor education is rigid and formal, often causing saturation and boredom when carrying out the process of teaching and learning activities. Whereas to get education is very important. Therefore, a learning system is needed that can eliminate the impression of saturation in the room. Based on Organic Architecture in the design used in natural schools, it also impacts the application of the material used. These materials are often found in areas / areas that are directly adjacent to the construction site, so as to provide ease of adjustment of the material with the surrounding nature. The method used is direct observation and literature study. The data management results are used as a basis for designing activities combined with the theme of Behavioral Insight Architecture. Thus, it is expected to be able to create a school that is environmentally comfortable and safe for its users.